Implementation of Modern Technologies in Teaching Foreign Languages - Hamidova Madinabonu Abduboriyevna (International Journal on Integrated Education, 2021)
The article describes issues based on studying modern methods of teaching foreign languages, which can be used in teaching, both in educational institutions and directly for self-study by anyone. The author studied certain types of programs that are used to introduce new ways of teaching. The technical component is highlighted, in which it is described with the help of what equipment the learning process can be performed. As well as, in the text of the article, special attention is paid to online learning using the Internet, its features and advantages are highlighted.